Discursive Approaches to Politics in Malaysia
XIV, 268 p. 26 illus., 9 illus. in color.
Keywords: This open access book examines Malaysian politics using a linguistic perspective. It explores how language serves to (de)legitimise governance, and its subsequent policies and activities in Malaysia. Grounded in discourse studies, this edited volume presents research on the discourses produced by and on Barisan Nasional, Pakatan Harapan and Perikatan Nasional from 2008 to 2020, studying how political actors (de)legitimise their governance through discursive means. The thirteen original chapters select spoken, print and digital texts in English, Malay, Mandarin and Tamil, and deploy varied theoretical and methodological approaches. Their linguistic analysis unearths the language features and strategies that facilitate (de)legitimation. It shows how political actors shape the discursive representation and evaluation of multiple concerns in Malaysia. Consequently, Discursive Approaches to Politics in Malaysia: Legitimising Governance improves our understanding of contemporary Malaysian political discourse. It is of interest to graduates and researchers in the field of discourse studies, seeking to understand the discursive contours of politics in this developing Asian country.